Water Content and Proximates in The "Gedong Kendal" Coffee Variety after Processed by Roasting Machine - Kriswanto, Kriswanto; Wiratama, Bayu; Wulansarie, Ria (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2020)
One of the coffee producers in Indonesia, namely Gedong Koffee Patean, still uses conventional roasting with uncontrolled temperature, resulting in uneven color and content. The variants of coffee beans available are Kopi Rakyat, Kopi Lanang, Robusta Fermentasi, Robusta Fermentasi 1, Excelsa Natural Dry, Robusta Natural Dry with different characteristics. The Godeng Kendal coffee association was given a roasting machine for roasting coffee bean products and analyzed for water, carbohydrate, protein and fat content The quality of coffee is affected by the roasting process with a 5 kg roasting machine which can be set to 200 for 25 minutes. The quality of coffee after roasting then has an average moisture content of 10.5%. Furthermore, the chemical properties of each variant were tested to obtain carbohydrate, protein, and fat content at the Laboratory of Biology. Analysis of carbohydrates using the Luff Schoorl method, protein using the kidney test, and fat using a soxhlet extractor. The test results show that the highest carbohydrate content is found in Robusta Fermentasi, which is 14.4%, the highest protein content is from Kopi Lanang, which is 26.6%. The lowest fat content is in natural dry coffee, with a fat content of 4.3%.